2020
DOI: 10.1075/ihll.26.11but
|View full text |Cite
|
Sign up to set email alerts
|

Afro-Peruvian Spanish declarative intonation

Abstract: This study offers an analysis of Afro-Peruvian Spanish (APS) declarative intonation. Our findings indicate that this dialect presents intonational features that diverge from other varieties of Spanish. It shows minimal downstepping across utterances and a predominant use of the L+H* pitch accent, even in prenuclear position, where L+>H* is more commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…This finding suggests that in PAS as spoken in Pucallpa, speakers consistently produce pitch accents across the whole utterance. This supports previous findings for PAS that found minimal deaccenting across declarative types (García 2023; this lack of deaccenting has also been reported in Afro-Hispanic varieties by Rao 2016 andButera et al 2020). Similarly, I found instances in which there was a F0 falling contour during the stressed syllable (H+L*), particularly in one-syllable words.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding suggests that in PAS as spoken in Pucallpa, speakers consistently produce pitch accents across the whole utterance. This supports previous findings for PAS that found minimal deaccenting across declarative types (García 2023; this lack of deaccenting has also been reported in Afro-Hispanic varieties by Rao 2016 andButera et al 2020). Similarly, I found instances in which there was a F0 falling contour during the stressed syllable (H+L*), particularly in one-syllable words.…”
Section: Discussionsupporting
confidence: 91%
“…When it comes to the larger body of literature on contact languages, this study reinforces some of the patterns found across contact situations in the Spanish-speaking world, specifically when it comes to tonal alignment in broad focus declaratives. The present findings raise important questions regarding whether these alignment patterns are the result of simply being contact varieties, a byproduct of universal processes of L2 acquisition (as claimed by Sessarego and Rao 2016;Butera et al 2020), or if/how specific languages in contact impact the intonational patterns of PAS. One possible venue for future research would be to examine the speech patterns of bilinguals of Spanish and Shipibo-Konibo, and to see how those compare to the speech patterns of monolingual Spanish speakers in the area.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We acknowledge the challenges of this approach-a tradeoff of working with spontaneous speech and a lack of control over what is being elicited-due to potential subjectivity and pragmatic nuances that could be at play, but trained researchers in this area have used similar approaches successfully, leading us to follow suit (see Butera et al 2020 We are grateful to Tomas Riad for his correspondence regarding such complexities.…”
Section: Conflicts Of Interestmentioning
confidence: 99%